Diatom Assemblage Changes in Agricultural Alluvial Plain Streams and Application for Nutrient Management. Issue 1 (1st January 2019) - Hicks, Matthew B.; Taylor, Jason M.
Abstract : In large, alluvial floodplains dominated by agriculture, small streams have the potential to experience nutrient enrichment affecting algal assemblage structure and metabolism. Nutrient enrichment is largely driven by application of nutrients and altered hydrologic regimes. To inform stressor–response‐based nutrient reduction goals for agricultural alluvial plain streams, diatom assemblages were sampled from 25 streams located within the Mississippi Alluvial Plain (MAP) with various land management practices and associated P and N inputs. From August through September 2015, epidendric diatom assemblage samples were collected from instream woody debris. Field nutrient gradients were skewed toward higher concentrations, and ranges of previously reported diatom assemblage response thresholds indicative of oligotrophic conditions were not well represented. Ordination analysis identified a gradient in species composition associated with increasing P and decreasing dissolved oxygen. A significant shift in diatom assemblage structure occurred when total P concentrations in the MAP streams exceeded 0.12 mg L− 1 . Phosphorus‐enriched systems were represented by a distinct set of indicator species, lower abundances of ubiquitous species, greater abundances of highly tolerant species, and greater abundances of high‐P indicator species. No relationships were observed among diatom assemblage measures or traits with increasing N. Current results do not address potential criteria for identifying high‐quality, oligotrophic streams. However, measures of diatom assemblage structure have potential for helping set benchmarks to reduce nutrient impacts and monitor effects of agricultural best management practices on MAP streams. Core Ideas: Identifying stream nutrient indicators is difficult in agricultural landscapes. Diatoms found in Mississippi Alluvial Plain streams are sensitive to changes in P concentrations. Diatom assemblages shifted when stream total P concentrations exceeded ∼0.12 mg L −1 . Diatom measures can help set nutrient reduction goals for agricultural streams. Stream diatom indicators may improve monitoring success of nutrient best management practices.